The methylenetetrahydrofolate reductase gene variant C677T influences susceptibility to migraine with aura - Rod A. Lea; Micky Ovcaric; James Sundholm; John MacMillan; Lyn R. Griffiths (2004)
The C677T variant in the methylenetetrahydrofolate reductase (MTHFR) gene is associated with increased levels of circulating homocysteine and is a mild risk factor for vascular disease. Migraine, with and without aura (MA and MO), is a prevalent and complex neurovascular disorder that may also be affected by genetically influenced hyperhomocysteinaemia. To determine whether the C677T variant in the MTHFR gene is associated with migraine susceptibility we utilised unrelated and family-based case-control study designs. A total of 652 Caucasian migraine cases were investigated in this study. The MTHFR C677T variant was genotyped in 270 unrelated migraine cases and 270 controls as well as 382 affected subjects from 92 multiplex pedigrees. In the unrelated case-control sample we observed an over-representation of the 677T allele in migraine patients compared to controls, specifically for the MA subtype (40% vs. 33%) (χ2 = 5.70, P = 0.017). The Armitage test for trend indicated a significant dosage effect of the risk allele (T) for MA (χ2 = 5.72, P = 0.017). This linear trend was also present in the independent family-based sample (χ2 = 4.25, P adjusted = 0.039). Overall, our results indicate that the T/T genotype confers a modest, yet significant, increase in risk for the MA subtype (odds ratio: 2.0 – 2.5). No increased risk for the MO subtype was observed (P > 0.05). In Caucasians, the C677T variant in the MTHFR gene influences susceptibility to MA, but not MO. Investigation into the enzyme activity of MTHFR and the role of homocysteine in the pathophysiology of migraine is warranted.